Systematic revision, cladistics and biogeography of the genus Neogutierrezia Martínez (Coleoptera :Scarabaeidae) and its phylogenetic placement in Rutelinae based on structural alignment of 28S rDNA sequences - Ocampo, Federico Carlos (2010)
The Argentinean endemic genus Neogutierrezia Martínez, 1953 (Scarabaeidae:Rutelinae) is revised and seven new species are described: N. bicolor Ocampo & Ruiz-Manzanos, sp. nov., N. chelii Ocampo & Ruiz-Manzanos, sp. nov., N. galileoi Ocampo & Ruiz-Manzanos, sp. nov., N. lagosae Ocampo & Ruiz-Manzanos, sp. nov., N. payuniensis Ocampo & Ruiz-Manzanos, sp. nov., N. scutata Ocampo & Ruiz-Manzanos, sp. nov. and N. variabilis Ocampo & Ruiz-Manzanos, sp. nov. Species status is proposed for N. affinis Martnez stat. nov., which was formerly considered as subspecies of N. mirabilis Martnez. The genus Neogutierrezia now includes 10 species distributed in the Monte biogeographic province in Argentina. In order to clarify the systematic placement of the genus Neogutierrezia, a molecular phylogenetic analysis was performed using structurally aligned 28S rDNA sequences (expansion segments D2 and D3) from 23 taxa in Scarabaeoidea, including two representative species of Neogutierrezia. This is the first report of an annotated secondary structure alignment of the D2 and D3 segments of 28S rRNA that spans a wide sample of scarabaeoids, providing a useful homology template for further phylogenetic reconstruction in these and closely related beetles. Results of the molecular parsimony analysis strongly indicate that the genus is closely related to members of the Rutelinae (Scarabaeidae), and thus Neogutierrezia Martínez is transferred from Melolonthinae: Pachydemini to Rutelinae, new placement. A morphological cladistic analysis of the genus was also undertaken, including all the 10 known species in the genus plus two outgroup taxa in Rutelinae, and based on 53 adult characters. The most-parsimonious cladogram provides evidence for the monophyly of the genus, which shows three main clades, distributed in Central Monte and Southern Monte. The adult morphology of the 10 species is described and a key is provided, along with illustrations of the diagnostic characters. The biogeography of species in the genus is discussed.